ANALISIS MINAT BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA KELAS IV DI SDN MEKARGALIH 4 (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to evaluate the level of interest in mathematics among fourth-grade students at SDN Mekargalih 04. Interest in mathematics is very important because it improves focus, persistence, and achievement of educational goals, but initial observations indicate a lack of student attention, engagement, and participation during learning. This study used a quantitative methodology with a survey, which included all 24 fourth-grade students as participants. Data were collected through a learning interest questionnaire using a Likert scale, which was arranged based on four indicators: enjoyment, attention, interest, and student engagement. The data were then analyzed descriptively by calculating the mean, median, mode, standard deviation, and frequency distribution and interest categories. The test results showed that the questionnaire instrument was valid and reliable (Cronbach Alpha 0.849), making it suitable for measurement purposes. The results revealed that no students were considered less interested or not interested; 16.7% were defined as very interested, 37.5% as interested, and 45.8% as moderately involved in mathematics learning. Interest in mathematics among fourth-grade students at SDN Mekargalih 04 was included in the interested category, mostly at a moderate interest level; Therefore, additional pedagogical initiatives are needed to improve the quality of mathematics learning experiences in the classroom.